Neuroprotective Effect of Boswellia serrata against 3-NP Induced Experimental Huntington's Disease - Kumar, Vinay; Sharma, Chanchal; Taleuzzaman, Mohamad; Nagarajan, Kandasamy; Haque, Anzarul; Bhatia, Mamta; Khan, Sumayya; Salkini, Mohamad A.; Bhatt, Pankaj (Current Bioactive Compounds, 2024)
Objectives: The study aimed to assess the neuroprotective effect of Boswellia serrata against 3-NP-induced experimental Huntington's disease. Background: Previous studies have shown Boswellia to have sedative, analgesic, and anti-tumour effects. Boswellia serrata yields four pentacyclic triterpene acids and boswellic acid, a bioactive substance that prevents leukotriene biogenesis. Methods: The potential neuroprotective effect of Boswellia serrata against 3-nitro propionic acid (3-NP)-induced Huntington's disease (HD) was examined at oral doses of 45 mg/kg, 90 mg/kg, and 180 mg/kg. In this study, HD was induced by 3-NP at a dose of 10 mg/kg in Wistar rats. The study used 56 Wistar rats (8 per group) for biochemical (inflammatory markers, acetylcholinesterase activity) and behavioural (elevated plus maze, Y-maze, open-field, tail suspension tests, etc.) assessments. Additionally, a histological examination of the brain was carried out. In addition, the analysis of Boswellia serrata extract was performed by different analytical techniques, like UV spectrophotometer, FTIR, and HPLC methods. Results: In the brain, succinate dehydrogenase is a mitochondrial enzyme irreversibly inhibited by 3-NP. Administration of 3-NP resulted in HD with altered behavioural and motor changes in rats. Treatment with Boswellia serrata resulted in remarkable protection of rats against 3-NP-induced behaviour and motor deficits in a dose-dependent manner. Moreover, in rats administered with 3-NP, Boswellia serrata improved memory performance and lowered levels of inflammatory biomarkers. These results have also been supported by histopathological analysis. Acetyl-11-keto-p-boswellic acid was found to be the main active component of Boswellia serrata extract. Conclusion: Boswellia serrata at a dose of 180 mg/kg exhibited better protection compared to the other doses against HD induced by 3-NP. More detailed studies based on molecular targets are needed for the Boswellia serrata to transition from the bench to the bedside for use as an adjuvant in HD patients.
Keywords: Boswellia serrata